IMPEDANCE REPRESENTATION OF TWO PHASE COMPOSITE MATERIALS AND EXPERIMENTAL MODELLING (Sciences & Technologie. B, Sciences de l'ingénieur, 2005)
This paper presents a nondestructive method enabling to characterize heterostructures or composite materials based on the equivalent electrical impedance. The heterostructures consist of a host dielectric material (a three-dimensional homogeneous matrix) and dielectric or conducting inclusions. We especially consider two examples of heterostructures used in building namely hollow materials and materials containing metallic tubes simulating for instance hollow bricks and pillars (or pylons) respectively. The mixture laws (i.e., the effective permittivity and resistivity) are also deduced in function of the concentration of inclusions and both the permittivity and resistivity of each component of the heterostructure. To illustrate this method, experimental validation is achieved on samples containing identical aligned inclusions, in the form of square section tubes, embedded in a polymer matrix and which are filled either by air or water. The results predicted by the proposed method are found in reasonable accordance with those obtained experimentally over a wide range of volume fraction of inclusions.